Voice Assistant Utilization among the Disability Community for Independent Living: A Rapid Review of Recent Evidence - Paola Esquivel; Kayden Gill; Mary Goldberg; S. Andrea Sundaram; Lindsey Morris; Dan Ding (Human Behavior and Emerging Technologies)
The rapid advancement and widespread adoption of voice assistance technology have shown promise in benefiting individuals with disabilities, offering increased social participation, independence, and leisure activities. However, barriers to their full utilization have been identified, leading to potential abandonment by users with disabilities. This rapid review is aimed at filling the gap in the literature by investigating the utilization of voice assistants among people with disabilities for independent living and community participation. A comprehensive search was conducted in academic literature databases, including PubMed, Embase, and Web of Science, and gray data was sourced from public social media domains through Infegy. The analysis included 48 articles and 281 social media posts that met the inclusion criteria. Neurodiversity, disabilities affecting vision, and general disabilities were the most frequently discussed categories in both sources. The most common tasks performed using voice assistants were interface control, reminders, and environmental control, with a focus on enabling independence. Barriers to use mentioned in the literature included cognitive load during use, speech interpretation, lack of nonverbal control, and privacy concerns, while gray data reported limited functionality and speech interpretation as primary barriers. Amazon Alexa was the most discussed brand in both sources. The findings highlight the need for further research and innovation to fully harness the potential benefits of voice assistants for individuals with disabilities. By addressing the identified barriers and tailoring voice assistance technology to cater to the specific needs of different disability types, this technology can become a powerful tool for enhancing the lives of individuals with disabilities and promoting greater independence and community participation.